Pengandaian Tokoh “Aku” dalam Puisi Lau Annanaa Lam Naftariq Karya Faruq Juwaidah (Analisis Semiotika Roland Barthes) / Supposition of "I" Figures in the Poetry “Lau Annanaa Lam Naftariq” by Faruq Juwaidah (Semiotic Analysis of Roland Barthes) - Lailiyatur Rohmah (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
هذا البحث يهدف إلى فهم المعاني واستكشاف المعاني في العلامة التي توجد في شعر لواننا .. لم نتفرق. تستخدم هذه دراسة تحليلية سيميائية لرولان بارت بمفهوم ترتيب الدلالة ، والتركيز على جوانب العلاقة بين دلالة الحرفية والمفهومية والخرافة. يوضح تحليل المعنى أن هذ الشعر مليئ بعمق المعنى والقيم الجمالية وجمال اللغة. تكشف نتائج هذه الدراسة أن التركيب العام للمعاني والعلامات الموجودة في شعر لواننا .. لم نتفرق هو افتراض الشخصية "أنا" ككائن يشير إلى الإنسان الذي يفترض عدم وجود الفصل ، "إذا لم نفصل" لمستوى دلالة حرفية التي تثير الحزن و الاضطراب العميق في شخصية "أنا" وظهور الآمال إلى مستوى دلالة مفهومية.الكلمة المفتاحية: الشعر لواننا .. لم نتفرق، تحليل سيميائية، رولان بارتAbstract:This research aims to understand and explore the meanings in the signs contained in the poem Lau Annanaa Lam Naftariq. This study used Roland Barthes' theory of semiotic analysis with the concept of order of signification, focusing on aspects of the relationship between denotation, connotation and myth. Meaning analysis shows that this poem is full of depth of meaning, aesthetic values and the beauty of the language. The result of this study reveal that the overall structure of meanings and signs found in Lau Annanaa Lam Naftariq's poetry is a supposition of the character "I" as an object that points to a human who presupposes no separation, "If we do not separate" as a denotation level that creates sadness and the deep turmoil of Aku character and the emergence of hopes became the level of connotation.